Patient’s Perspectives Regarding Use and Misuse of Antibiotics; A Cross Sectional Study - Aleem, Saima; Asif, Muhammad; Bahadur, Sher; Mushtaq, Muneeba; Hassan, Walid (Journal of Liaquat University of Medical & Health Sciences, 2021)
Objective: To understand and evaluate the perspectives of patient regarding use and misuse of antibiotics. Methodology: This cross-sectional study was conducted at rural health center SANN from November 2018 to May 2019. Both male and female patients over the age of 15 years were included in this study subjected to their willingness by convenient sampling. Sample size was 628. A self- structured questionnaire was used for data collection. Data was analyzed using SPSS Version-24 Results: Sample size was 628 out of which 43.2% were male (n=271) and 56.8% were female (n=357). Around 65% responded that antibiotics were always safe to use and 79% responded that they take antibiotics from friends and family without even consulting medical practitioner and 72% had purchased antibiotics even without prescriptions. Self-request for unnecessary prescriptions of antibiotics was reported by 83% of the respondents. Conclusion: This specific study reflects a gap regarding the appropriate knowledge about usage of antibiotics and owing to this the misuse is likely to happen. Keywords: Perspectives, Antibiotics, Misuse, Resistance